Kolaborasi Mahasiswa Kuliah Kerja Nyata Kelompok 78 dan Masyarakat dalam Meningkatkan Kebersihan Masjid dan Pengelolaan Lingkungan Makam Desa Bukit Peninjauan II - Pratama, Fikri Yoga; Rahcman, Anita; Wulandari, Eka; Ananda, Firli Ersa; Surati, Iis; Wulandari, Wulandari; Gunawan, Candra; Nurjanah, Nana Aprilia; Saputra, Randika Wahyu (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Community service through Real Work Lectures (KKN) is one form of student contribution in overcoming problems in society. This research aims to examine the role of KKN in increasing environmental awareness and providing education to children in Bukit Peninjauan II Village, Seluma Regency. The method used in this research is observation. KKN students participated in activities to clean the mosque environment, providing education about the importance of maintaining cleanliness, as well as managing the grave environment. The research results show that through KKN, environmental awareness in Bukit Peninjauan II Village has increased significantly. People are starting to understand how important it is to maintain cleanliness and care for the environment around them. The children also showed increased knowledge about the importance of protecting the environment through activities to clean the mosque environment and grave management carried out by KKN students.